2020
DOI: 10.3390/ijerph17197241
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Behavioral Consequences of the COVID-19 Pandemic: The Role of Health Anxiety, Intolerance of Uncertainty, and Distress (In)Tolerance

Abstract: The COVID-19 pandemic represents a worldwide threat to mental health. To optimize the allocation of health care resources, research on specific vulnerability factors, such as health anxiety, intolerance of uncertainty, and distress (in)tolerance, and particularly their effect on the time course of SARS-CoV-2 related anxiety appears crucial for supporting high risk groups suffering from elevated mental distress during the pandemic. N = 887 participants (78.4% female; Mage = 38.15, SD = 17.04) completed an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 68 publications
11
69
1
1
Order By: Relevance
“…Therefore, a multidisciplinary approach which also includes the psychological aspect, should be considered by the worldwide health policy makers [58]. It is also important to note that the groups that present a greater risk and fear perception are those that need the most support [59] and, therefore, require more complex investigations that place the focus of their objectives on it.…”
Section: Applicability Of the Results And Future Lines Of Researchmentioning
confidence: 99%
“…Therefore, a multidisciplinary approach which also includes the psychological aspect, should be considered by the worldwide health policy makers [58]. It is also important to note that the groups that present a greater risk and fear perception are those that need the most support [59] and, therefore, require more complex investigations that place the focus of their objectives on it.…”
Section: Applicability Of the Results And Future Lines Of Researchmentioning
confidence: 99%
“…Recent publications have cited or speculated about the impact of numerous determinants associated with mental health outcomes during the COVID-19 pandemic. These have included having personal protective equipment and infection control needs met, fear of stigma or discrimination for working as a HCW, fear of spreading disease to a family member, domestic caregiver status, uncertainty regarding mode of disease transmission, income loss, perceived susceptibility, and vaccine availability, safety and uptake hesitancy [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. These factors are all likely highly important, and we are not able to opine on which ones were most relevant in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that people scoring higher on health anxiety will be more concerned with the physical health consequences of COVID-19, whereas people scoring higher on intolerance of uncertainty may be more concerned with the uncertainty of the further development of the pandemic and its socio-economic consequences. Indeed, multiple previous studies have found a relationship between fear of COVID-19 and health anxiety ( Fedorenko et al, 2021 ; Jungmann & Witthöft, 2020 ; Mertens et al, 2020 ; Sauer et al, 2020 ; Wheaton et al, 2021 ) and between fear of COVID-19 and intolerance of uncertainty ( Bakioğlu et al, 2020 ; Elsharkawy & Abdelaziz, 2020 ; Fedorenko et al, 2021 ; Satici, Saricali, et al, 2020 ; Wheaton et al, 2021 ). However, it remains unclear how these two anxious personality traits relate to different types of fear of COVID-19.…”
Section: Introductionmentioning
confidence: 95%